ANALISA TEGANGAN SISTEM PERPIPAAN BONGKAR MUAT KAPAL TANKER MT. AVILA 6300 DWT DENGAN MENGGUNAKAN PERANGKAT LUNAK CAESAR II v5.10. - Yudo, Hartono (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2010)
Pipe stress analysis (piping stress analysis) is more directed to the analysis of flexibility and stress that occur as a result of the force and the expenses incurred pipe (system) in a state of work or ready (steady). In order, system can work optimally and safely in accordance with applicable standards.In this paper, using two modifications to reduce stresses that occurs in the loading and unloading piping system of MT. Avila 6300 DWT using software caesar II v5.10. First, modifications ware made is modification to eliminate overstress can be done by considering the distance by changing the type ofÂ  support in accordance with the movement of the pipe that occurred (deflection). Second is modification ware made based on calculations of allowable pipe span formulas, then with the analysis by using software CAESAR II v5.10 we can compare and determine the best model of piping systems for MT. Ãvila 6300 DWT tanker ship vessel.